Selected issues concerning the multilateral trading system - Acharya, Rohini (WTO GenevaCH, 2004)
Highlights a misconception regarding the causes of trade imbalances. Considers tariff 'peaks' and tariff escalation, together with special and differential treatment. Evaluates the rationale for a high degree of support for agriculture. Deals with market access concerns of developing countries in textiles and clothing. Discusses issues concerning barriers to trade such as anti-dumping, technical standards and SPS measures. Considers market issues in services.